Lithiated Nanoparticles Doped with Ionic Liquids as Quasi-Solid Electrolytes for Lithium Batteries. (1st June 2019) - Bertasi, Federico; Pagot, Gioele; Vezzù, Keti; Nale, Angeloclaudio; Pace, Giuseppe; Herve Bang, Yannick; Crivellaro, Giovanni; Negro, Enrico; Di Noto, Vito
Abstract: This work reports two quasi-solid composite electrolytes based on LiFT (Lithiated Fluorinated Titania) nanopowder and either 1-ethyl-3-methylimidazolium tetrafluoroborate (EMImBF4 ) or 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMImTFSI) ionic liquid (IL). In details, LiFT nanopowder is doped with ca . 30 wt% of IL, giving rise to materials with formula LiFT/(EMImBF4 )0.183 and LiFT/(EMImTFSI)0.087 . The resulting composite electrolytes appear as powder-like solids as the IL is completely absorbed by LiFT. The correlation between structure, thermal properties and long-range charge migration processes of the here proposed electrolytes is investigated by several characterization techniques, as follows: i) differential scanning calorimetry (DSC) and high-resolution thermogravimetry (HR-TGA); ii) Fourier-transform infrared spectroscopy in both the medium and the far infrared (FT-MIR and FT-FIR); and iii) broadband electrical spectroscopy (BES). The conductivity of the here proposed composite electrolytes is promising. Indeed, at 30 and 100 °C it corresponds respectively to 1.75 × 10 −3  S cm −1 and 1.05 × 10 −2  S cm −1 for LiFT/(EMImBF4 )0.183, and 1.36 × 10 −2  S cm −1 and 4.42 × 10 −2  S cm −1 for LiFT/(EMImTFSI)0.087 . Finally, LiFT/(EMImTFSI)0.087 is used to fabricate a coin cell prototype, that is tested by galvanostatic cycling for performance and durability. Highlights: Two composite electrolytes are obtained, appearing as powder-like solids. Li + BF4 − and [Li(TFSI)2 ] - are formed owing to the dissociation of Li + from LiFT component. At 30 °C a conductivity of 1.36 × 10 −2  S cm −1 is achieved by LiFT/(EMImTFSI)0.087 . Li + are exchanged between LiFT nanoparticles and among adjacent ionic aggregates. Battery cycling is achieved using a quasi-solid composite electrolyte.